E-Liquid Containing a Mixture of Coconut, Vanilla, and Cookie Flavors Causes Cellular Senescence and Dysregulated Repair in Pulmonary Fibroblasts: Implications on Premature Aging - Lucas, Joseph H.; Muthumalage, Thivanka; Wang, Qixin; Friedman, Michelle R.; Friedman, Alan E.; Rahman, Irfan (Frontiers in Physiology, 2020)
Electronic cigarette (e-cig) usage has risen dramatically worldwide over the past decade. While they are touted as a safe alternative to cigarettes, recent studies indicate that high levels of nicotine and flavoring chemicals present in e-cigs may still cause adverse health effects. We hypothesized that an e-liquid containing a mixture of tobacco, coconut, vanilla, and cookie flavors would induce senescence and disrupt wound healing processes in pulmonary fibroblasts. To test this hypothesis, we exposed pulmonary fibroblasts (HFL-1) to e-liquid at varying doses and assessed cytotoxicity, inflammation, senescence, and myofibroblast differentiation. We found that e-liquid exposure caused cytotoxicity, which was accompanied by an increase in IL-8 release in the conditioned media. E-liquid exposure resulted in elevated senescence-associated beta-galactosidase (SA-β-gal) activity. Transforming growth factor β1 (TGFβ1) induced myofibroblast differentiation was inhibited by e-liquid exposure, resulting in decreased α-smooth muscle actin and fibronectin protein levels. Together, our data suggest that an e-liquid containing a mixture of flavors induces inflammation, senescence and dysregulated wound healing responses.